(untitled) (Journal of Hama University, 2022)
Introduction: Complete dentures require many clinical and laboratory stages to fabricate. Many attempts to facilitating or shortening these stages, recording jaw relations in final impressions stage considered as a one of these attempts, and a number of methods have been mentioned for this procedure. One of these methods is that the gothic arch tracing device is attached to the final impressions in order to integrate the two stages of final impressions and recording jaw relations, whereas the gothic arch tracing device is used to record the position of the centric relation, which is the reference horizontal position in edentulous patients. Centric relation record is considered as a one of the most sensitive and rigorous procedure in extensive oral rehabilitation cases and the success of complete denture depends largely on the correct recording of this position. Therefore, caution must be taken and reliable scientific methods must be followed while recording this position. Purpose: The aim of this research was to radiography study the centric relation record between gothic arch tracing method at final impressions stage and traditional method in complete dentures patients. Materials and Methods: sample included 12 edentulous patients. they were all males, and their ages ranged between 48 and 73 years. The preliminary and final impressions were made by the common methods, and PVS silicone with various viscosities used as the final impression material. Gothic arch tracer was then attached to the custom trays and the centric relation was recorded at the same stage with the final impressions. After boxing and casting the final impressions, acrylic record bases and wax occlusal rims were made, and the centric relation were recorded in the traditional way. The artificial teeth were arranged for both methods of recording centric relation, and then CBCT was used to study the position of the articular condyles within the gleniod fossa in both methods. Results: There were no statistically significant differences in the frontal and sagittal placement of the articular condyles between the two methods of recording centric relation, except for the amount of medial articular distance at the right condyle. Conclusions: There was no effect on centric relation record between gothic arch tracing method at final impressions stage and traditional method.